2009
DOI: 10.1021/jp810612x
|View full text |Cite
|
Sign up to set email alerts
|

Additivity of Substituent Effects. Core-Ionization Energies and Substituent Effects in Fluoromethylbenzenes

Abstract: Carbon 1s ionization energies have been measured for all of the carbon atoms in eight fluoromethylbenzenes. Enthalpies of protonation have been calculated for protonation at all of the ring carbons in the same molecules. These data together with previously reported data on fluorobenzenes and methylbenzenes provide the basis for studying the additivity of substituent effects and the correlation between enthalpies of protonation with core-ionization energies. Although a linear additivity model accounts reasonabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 42 publications
(58 reference statements)
4
20
0
1
Order By: Relevance
“…Atom ical approach that can reproduce the adiabatic and vertical C1s ionization energies of the molecules, observed [16][17][18][19][20][21] with the new generation synchrotrons, as accurately as possible.…”
Section: Moleculementioning
confidence: 99%
See 4 more Smart Citations
“…Atom ical approach that can reproduce the adiabatic and vertical C1s ionization energies of the molecules, observed [16][17][18][19][20][21] with the new generation synchrotrons, as accurately as possible.…”
Section: Moleculementioning
confidence: 99%
“…The authors who published the observed Table 5 Calculated and observed adiabatic and vertical C1s core electron binding energies, in eV, of some methyl-fluoro-substituted benzenes without (C rel = 0 eV) and with (C rel = 0.05 eV) relativistic correction. [21]. b Average absolute deviation in eV.…”
Section: Calcmentioning
confidence: 99%
See 3 more Smart Citations